All Days 2012
DOI: 10.2118/149780-ms
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Mathematical Optimization and Decision Making in Intelligent Fields

Abstract: In this paper a decision-making approach that can be applied to problems that are relevant to the oil and gas industry is presented. This methodology is supported by state-of-the-art mathematical optimization algorithms, and is based on the formal integration of the decisions in question with well-studied optimization procedures. The integration of the methodology with the application adds to its robustness. Two different types of problems are formulated and solved. The first kind is based on deciding which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…The optimization problems in the two cases presented can be approached by use of derivative-free methods (Conn et al 2009;Echeverría Ciaurri et al 2011;Kramer et al 2011)-which can be computationally expensive, but they often perform efficiently when the number of optimization variables is very small-or gradient-based techniques combined with numerical gradients, because (exact) derivative information may be difficult to obtain in reservoir-flow simulators when field-plateau rates are considered as control variables. We can expect that the computational cost associated with the solving (within acceptable practical accuracy) of an optimization problem that presents only one variable will be in most situations relatively small (e.g., no more than 10 objective-function evaluations).…”
Section: (Bottom Right)mentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization problems in the two cases presented can be approached by use of derivative-free methods (Conn et al 2009;Echeverría Ciaurri et al 2011;Kramer et al 2011)-which can be computationally expensive, but they often perform efficiently when the number of optimization variables is very small-or gradient-based techniques combined with numerical gradients, because (exact) derivative information may be difficult to obtain in reservoir-flow simulators when field-plateau rates are considered as control variables. We can expect that the computational cost associated with the solving (within acceptable practical accuracy) of an optimization problem that presents only one variable will be in most situations relatively small (e.g., no more than 10 objective-function evaluations).…”
Section: (Bottom Right)mentioning
confidence: 99%
“…General constraints could be dealt with by means of the introduction of a constraint-violation measure (in addition to the production-potential measure) combined with techniques inspired by the filter method for constrained optimization (Fletcher and Leyffer 2002;Echeverría Ciaurri et al 2011). Field-rate constraints (e.g., maximum field-fluid-production rate) may be transformed into well constraints through heuristics based on productivity/injectivity measures.…”
Section: (Bottom Right)mentioning
confidence: 99%
“…The problem of finding the optimum, real-time, ICV control setting has now become a complex, multidimensional, non-linear problem. (Echeverria-Ciaurri et al, 2012) have provided a good overview of the available control optimization methods. They also suggested that the selection of a suitable optimization method should include upscaling, parameterization, conditioning and identification of a suitable control algorithm.…”
mentioning
confidence: 99%